Inheritance of Body Color in the Brown Planthopper, Nilaparvata lugens - Barrion, A.A.; Saxena, R.C. (Wiley, 1987)
The segregation frequencies of color phenotypes of F1, F2, and backcross progenies revealed that the body coloration of the brown planthopper, Nilaparvata lugens (Stål), exhibited multiple allelism. Monogene for color morphism exists in three allelic forms > ‐b+ (brown or wild type), b° (orange) and bb (black). The dominance relationship was bb > b+ > b°. The relationship between phenotype and genotype in N. lugens was not fixed. The six possible genotypes produced eight phenotypes.RÉSUMÉHérédité de la couleur du corps chez Nilaparvata lugens Stål (Homoptère: Delphacidae)Les fréquences de ségrégation des différentes colorations de F1, F2 et des croisements en retour ont montré que la coloration du corps de Nilaparvata lugens est due à un multi‐allèlisme. Le monogène pour la couleur existe sous trois formes allèliques: b+ (brun ou sauvage), b° (orange) et bb (noir). Les relations de dominance étaient: bb > b+ > b°. On n'a pas établi les relatios entre phénotypes et génotypes chez N. lugens. Les 6 génotypes possibles produisent 8 phénotypes.